NEW RESULTS ON FIXED POINT THEOREMS IN 2-BANACH SPACES (Balkan Journal of Applied Mathematics and Informatics, 2025)
In this article, we prove a common fixed point result for interpolativeKannan type contraction mappings in 2-Banach spaces. On the other hand, weintroduce interpolative Dass and Gupta rational type contraction mappings on2-Banach spaces. In particular, we discuss the existence of a fixed point of sucha mapping in 2-Banach spaces.
Keywords: Fixed point theorems, 2-Banach spaces, complete metric spaces.